Over the Horizon : Time, Uncertainty, and the Rise of Great Powers - Edelstein, David M. (Book collections on Project MUSE., 2017)
How do established powers react to growing competitors? The United States currently faces a dilemma with regard to China and others over whether to embrace competition and thus substantial present-day costs or collaborate with its rivals to garner short-term gains while letting them become more powerful. This problem lends considerable urgency to the lessons to be learned from Over the Horizon. David M. Edelstein analyzes past rising powers in his search for answers that point the way forward for the United States as it strives to maintain control over its competitors. Edelstein focuses on the time horizons of political leaders and the effects of long-term uncertainty on decision-making. He notes how state leaders tend to procrastinate when dealing with long-term threats, hoping instead to profit from short-term cooperation, and are reluctant to act precipitously in an uncertain environment. To test his novel theory, Edelstein uses lessons learned from history's great powers: late nineteenth-century Germany, the United States at the turn of the twentieth century, interwar Germany, and the Soviet Union at the origins of the Cold War. Over the Horizon demonstrates that cooperation between declining and rising powers is more common than we might think, although declining states may later regret having given upstarts time to mature into true threats.